Traumatized Perception of the Self and Time in Ian McEwan's The Cement Garden and The Child in Time - Ayyildiz, Nilay Erdem (Istanbul Univ, Fac Letters, 2022)
The purpose of this study is to decipher the relationship between trauma and the differentiating perception of the self and time by discussing varying post-traumatic responses of the traumatized characters in Ian McEwan's The Cement Garden (1978) and The Child in Time (1987). To this end, the study applies trauma theory to examine the traumatized characters' altered perception of temporality and the self, and to discuss to what extent the characters in the novels can overcome the impacts of the traumatic experiences they have. The two novels revolve around traumatized victims that lose the conscious perception of the self and temporality in reality after the traumatic experience. The Cement Garden depicts the post-traumatic challenges of four siblings, called Jack, Julie, Tom and Sue after their mother's death. The Child in Time unveils Stephen and Julie's process of working through their ordeal after the disappearance of their little daughter, Kate in parallel to Stephen's friend Charles's acting out his traumatic childhood by regressing to his boyhood. The critical approach to the characters' response to their traumas concludes that trauma disrupts people's perception of time and the self, leading either to tragedy when they lose the balance between their defense mechanisms and the trauma reality, or to awakening to their renewed life when they reconcile with their trauma reality.
Keywords: Trauma; Ian McEwan; The Cement Garden; The Child in Time; temporality